Pemanfaatan Ampas Bubuk Kopi Robusta Sebagai Campuran Bahan Baku Pembuatan Bokasi - Irfan, Irfan; Bakhtiar, Bakhtiar; Putra, Remmy Lazuardi; Fadhil, M. (Agriculture Faculty, 2024)
Most of the coffee grounds waste is still left unattended so that it can pollute the environment. For this reason, it is necessary to have a way to use coffee grounds, such as making organic fertilizer or bokashi, in order to reduce environmental pollution and at the same time reduce the use of chemical fertilizers by farmers. The decomposition of coffee grounds tends to produce acid and lowers the pH of bokashi, so it is necessary to add alkaline ingredients. This research aimed to study the effect of the proportion of coffee grounds and fish bone meal as a mixture of raw materials in making bokashi on the quality of the bokasi produced. This research used a Completely Randomized Design (CRD) with 2 factors. Factor I proportion of coffee grounds (A: 0%, 10%, 20%, 30%). Factor II proportion of fish bone meal (T: 0%, 2,5%, 5%). Each treatment was repeated 2 times to obtain 24 experimental units. The analysis of bokashi included: total microorganisms (TCC), pH, C elements, N elements, C/N ratio, temperature, water content, and plant growth tests. The results showed that coffee grounds could be added to the raw material mixture for making bokashi up to a proportion of 30%, indicated by a good pH (neutral range) and C/N ratio (10-20) values of bokashi produced. However, plant height generally decreased. The addition of up to 5% fish bone meal in raw material mixture which contained coffee grounds could help to maintain or increase the pH of bokashi during the fermentation process, and improved plant growth.